47. Long Term Outcomes of Pulse-taper Corticosteroid Therapy (PCT) for Refractory Non-HIV Cryptococcal Meningoencephalitis. (31st December 2020) - Anjum, Seher; Williamson, Peter; Magone, Teresa; Edmond, Fitzgibbon; Krieger, Chantal; Murphy, Elizabeth; Zalewski, Chris; King, Kelly; Chisholm, Jennifer; Brewer, Carmen; Nath, Avindra; Billioux, Jean; et al.
Abstract: Background: Cryptococcal meningoencephalitis (CM) is a major cause of mortality in HIV/AIDS, transplant recipients and previously healthy individuals. In the latter, a post-infectious inflammatory response syndrome (PIIRS) is associated with poor clinical response despite prior amphotericin therapy and CSF culture conversion. Data on effective treatment is limited. Methods: Between March 2015 and March 2020, 15 patients with CM/PIIRS were treated with adjunctive pulse – taper corticosteroid therapy (PCT) consisting of intravenous methylprednisolone 1 gm daily for 1 week followed by oral prednisone 1 mg/kg/d, tapered based on clinical and radiological response plus oral fluconazole. Montreal cognitive assessments (MOCA), Karnofsky Performance scores, MRI brain scans, eye and audiologic exams were conducted at baseline and after pulse completion. CSF parameters were assessed prior to and after the pulse. Results: 80% of patients were male, median age 51 years. Median time from antifungal treatment to steroid initiation was 6 weeks. The most common symptoms at PIIRS diagnosis were progressive deterioration in mental status and vision changes. There was a significant improvement in MOCA(n=14) and Karnofsky(n=15) scores at 3 weeks (p< 0.0003), which was accompanied by improvements in CSF: serum, glucose ratios, CSF WBC, protein and activated CD4 T cells (n=14) post-pulse (p< 0.003). Additionally, soluble CSF IL-6 and sCD25 levels improved (p = 0.03). Neurofilament light chain levels (NFL), a biomarker of axonal damage, showed significant reductions over a 30-month period (Generalized Estimating Equation coefficient = 0.128) and a negative correlation with post pulse MOCA scores (r = - 0.8; p = 0.01). Papilledema (n=8) and visual field deficits (n=11) improved significantly (p< 0.0005) after 2 months of pulse completion. Brain MRI showed improvement of radiological findings in 11 patients (p=0.001). Five out of 7 patients who underwent audiological testing demonstrated hearing improvement after 3 weeks post-pulse. CSF cultures remained negative. Conclusion: PCT in this small cohort of PIIRS patients was associated with persistent improvements in CM-related complications with minimal toxicity and no recurrence of infection. Disclosures: All Authors : No reported disclosures